From scientifically based research to evidence based learning - Rosa Cera (University of Bologna, 2016)
This essay is a reflection on the peculiarities of the scientifically based research and on the distinctive elements of the EBL (evidence based learning), methodology used in the study on the "Relationship between Metacognition, Self-efficacy and Self-regulation in Learning". The EBL method, based on the standardization of data, explains how the students' learning experience can be considered as a set of "data" and can be used to explain how and when the research results can be considered generalizable and transferable to other learning situations. The reflections present in this study have also allowed us to illustrate the impact that its results have had on the micro and macro level of reality. They helped to fill in the gaps concerning the learning/teaching processes, contributed to the enrichment of the scientific literature on this subject and allowed to establish standards through rigorous techniques such as systematic reviews and meta-analysis.